Information System Audit for Tangerang Live Application Using Cobit 5 Domain EDM dan APO Framework - Dwi, Rosmawati; Afrijaldi, Rizki; Darmawan, Aden Andre; Alamsyah, Muhammad Luki; Auliya, Nur (Universitas Raharja, 2025)
The Central Government has the ambition to make Indonesia the fourth-largest in the world's economic power through the vision of Indonesia Emas 2045. To achieve this goal, there is a need for the improvement of public services and rapid restructuring of population administration. Within this framework, Tangerang Live, introduced by the Tangerang City Government on August 17, 2016, is designed to provide online services in the fields of population, education, and healthcare. The success of public services is measured as an indicator of Good Governance, with more than 500 thousand users currently, and downloads show an increase influenced by the quality of services and initiatives from the Tangerang City Communication and Informatics Agency. This research aims to evaluate the implementation of IT governance in Tangerang Live, with data collection using Literature Review and Questionnaire through Gform with 24 respondents. This research method refers to the COBIT 5 model, focusing on two COBIT 5 domains, namely EDM and APO, consisting of five subdomains: EDM02, EDM03, APO04, APO05, and APO11. The results of the information system audit on Tangerang Live show an average Maturity Score of 3.77, with details of EDM02 3.74, EDM03 3.75, APO04 3.94, APO05 3.61, and APO11 3.82. In conclusion, the scores generated are at level 4 (managed), indicating that the overall implementation of information technology is quite good, although there are some recommendations for improvement, especially in the APO05 subdomain related to user data management and the efficiency of data usage. These improvements are necessary to enhance the quality of services for Tangerang Live users.